Tinjauan Pengelolaan Arsip di Bagian Unit Administrasi Rumah Sakit Bhayangkara TK II Sartika Asih Bandung - Ruid, Jumaison Yepta; Ariyani, Nurul Dwi (Barongko: Jurnal Ilmu Kesehatan, 2023)
This study aims to determine the Management of Archives in the Administration Unit of Bhayangkara TK II Sartika Asih Hospital Bandung. The method used in this study is a qualitative method with a descriptive approach, while the data collection technique is carried out by observation, interview and literature study. In this study, researchers found problems that occurred in archive management such as (1) Accumulation of letters (2) Inadequate facilities and infrastructure (3) Lack of attention to the storage system (4) Unavailability of archive borrowing cards (5) Lack of maintenance and cleanliness of archives. Based on the problems that occurred above, the researcher tried to provide several suggestions as follows: (1) Minimize the scheduling of incoming mail because it can cause delays in the distribution of letters, (2) Increase the number of cabinets and the separation of the archive room itself, (3) Affirm the 1-door system policy and make SOP for the archive storage system, (4) Apply the procedure for borrowing archives so that archives are not lost, (5) Maintain archives to avoid dust and insects.